The Link between Productivity and Labour Compensation in Selected Central and Southeast European Countries - Trenovski, Borce; Tashevska, Biljana; Kozheski, Kristijan; Merdzan, Gunter (Faculty of Economics in Banja Luka, 2019)
The link between labor productivity and labor compensation has been of great interest in economic research. The traditional economic theory argues that there is a positive link between productivity and workers’ compensation. According to this theory, increasing labor productivity will cause an increase in the wage level and will boost the average household purchasing and consumption power. However, many research studies addressing this issue indicate a weakening of the link between labor productivity and compensation received by employees, with a rising divergence since the 1980s, when labor productivity started growing faster than real wage. The purpose of this research is to analyze the extent of the decoupling phenomenon in selected CEE countries compared to Western European countries. In this respect, the paper attempts to explore the causal relationship between productivity and real labor compensation and offer empirical evidence for the existence of the so-called Great decoupling between the two variables.
Keywords: Productivity; labor market; decoupling; regression analysis; European Union countries